Nulliparity is associated with less healthy markers of subclinical cardiovascular disease in young women with overweight and obesity. (10th April 2015) - Niemczyk, Nancy Anderson; Catov, Janet M.; Barinas‐Mitchell, Emma; McClure, Candace K.; Roberts, James M.; Tepper, Ping G.; Sutton‐Tyrrell, Kim
<x xml:space="preserve">Abstract</x> Objective Higher parity is associated with increased subclinical cardiovascular disease (CVD) in mid‐life and older women and with increased CVD risk overall. The relationship between parity, subclinical CVD, and infertility in young women with overweight and obesity has been infrequently evaluated. Methods Reproductive histories were obtained in 191 (66%) young women with overweight and obesity (BMI 25‐39.9 kg/m2) participating in a weight loss trial. Baseline carotid intima‐media thickness (IMT) and inter‐adventitial diameter (IAD) were assessed via B‐mode ultrasound. Linear regression was used to estimate the relationship between parity and carotid measures, adjusted for demographic, cardiovascular, and reproductive risk factors. Results Nulliparous women (n = 70, age 34.9 ± 7.1) had increased common carotid IAD (0.230 mm, SE 0.08, P = 0.003) and mean common carotid artery (CCA) IMT (0.031 mm, SE 0.01, P = 0.007) compared with parous women (n = 102, age 39.5 ± 4.9), persisting after adjustment for age, race, and CVD risk factors. No other reproductive factors were statistically significantly associated. Conclusions Nulliparity is associated with markers of less healthy carotid arteries in a sample of disease‐free 25‐ to 45‐year‐old women with overweight or obesity. This may represent a beneficial effect of pregnancy or indicate overall better health in women with overweight/obesity who are capable of childbearing.